2020
DOI: 10.1021/acs.nanolett.9b05003
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Rewritable Frequency Tuning of a Nanoelectromechanical Resonator Using Photoinduced Doping

Abstract: Tuning the frequency of a resonant element is of vital importance in both the macroscopic world, such as when tuning a musical instrument, as well as at the nanoscale. In particular, precisely controlling the resonance frequency of isolated nanoelectromechanical resonators (NEMS) has enabled innovations such as tunable mechanical filtering and mixing 1 as well as commercial technologies such as robust timing oscillators 2 . Much like their electronic device counterparts, the potential of NEMS grows when they a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Here, we experimentally demonstrate a low-loss and rewritable PIC platform using laser-written Sb 2 S 3 . A dielectric-assisted waveguide structure 8,26 is used to lower the optical propagation loss while enhancing the endurance and reliability of PCMs. We first demonstrate arbitrary patterning on the PCM canvas with a fine resolution of 600 nm line pitch, to demonstrate the rewritable capability of our platform, then write laser-written waveguides between pairs of predefined grating couplers.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we experimentally demonstrate a low-loss and rewritable PIC platform using laser-written Sb 2 S 3 . A dielectric-assisted waveguide structure 8,26 is used to lower the optical propagation loss while enhancing the endurance and reliability of PCMs. We first demonstrate arbitrary patterning on the PCM canvas with a fine resolution of 600 nm line pitch, to demonstrate the rewritable capability of our platform, then write laser-written waveguides between pairs of predefined grating couplers.…”
mentioning
confidence: 99%
“…The propagation loss was then measured via a cutback measurement as 0.01722 dB/μm, comparable to the 0.010 dB/μm loss in simulation. 8 While this loss is ∼1000 times larger than current commercial silicon photonic waveguides, 27 this loss is acceptable to create waveguides of submm length. Our rewritable and low-cost platform shows a promising path to democratizing PIC prototyping for designers without access to a nanofabrication facility, which will enhance PIC education and accelerate rapid PIC prototyping.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a small-size membrane operating at low frequencies with reasonable bandwidth and displacement amplitude has implications for ultrasonic and audio transduction. Previous studies have shown that electric field gating and photodoping can tune the resonant frequency of a graphene mechanical transducer, but these methods are more effective in upshifting, rather than downshifting, the resonant frequency. Furthermore, the bandwidth of a graphene transducer normally shrinks (quality factor, Q , increases) when the resonant frequency is decreased because of reduced energy dissipation, and the displacement amplitude ( d ) of the vibrating membrane also decreases with the reduced membrane radius ( r ) as , …”
mentioning
confidence: 99%